Do near-beginner learners of French have any writing strategies? - Macaro, E (Routledge, 2007)
This article reports on a descriptive and exploratory study of near-beginner learners of French in English secondary schools, their cognitive and metacognitive strategies, and their general approaches to writing. There is virtually no research on foreign language writing at this level, conceived in this study as including the copying of words and sentences, as well as free-writing. 16 students took part in task-based interviews designed to elicit their writing strategies at two time points some seven months apart. An analysis of their writing behaviours shows that being able to write was associated with being able to read, that there was some variation in the extent to which students were concerned with meaning whilst copying, that in both copy-writing and free-writing students attempted to use grapheme–phoneme correspondences (GPC) but with little success, and that few students developed a capacity to write freely on a topic.